Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21089/njhs.43.0113
|View full text |Cite
|
Sign up to set email alerts
|

How Obesity Affects Our Health

Abstract: Introduction: Obesity is a form in which there is fat collection of body overweight or adipose tissue. This accumulation happens in lean body mass of muscles and unlike connective tissue. Obesity is consummate constantly defined by the body mass index (BMI), a mathematically formula of weight-for-height index. BMI has a high interaction with adiposity and it interacts well with fat weight at the population rank. Obesity is defined as abnormal all excessive accumulation that may be harmful to health. Although, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…Race-specific characteristics of body composition imply that the relation between obesity and CVRFs may also be different among races [32]. Epidemiological surveys and population health promotion usually take BMI as a useful indicator for measuring whole-body obesity, which is associated with chronic diseases such as dyslipidemia [45,46]. Hu et al [47] found that a higher BMI was directly associated with higher levels of TG in rural Chinese people aged 20-70 years.…”
Section: Discussionmentioning
confidence: 99%
“…Race-specific characteristics of body composition imply that the relation between obesity and CVRFs may also be different among races [32]. Epidemiological surveys and population health promotion usually take BMI as a useful indicator for measuring whole-body obesity, which is associated with chronic diseases such as dyslipidemia [45,46]. Hu et al [47] found that a higher BMI was directly associated with higher levels of TG in rural Chinese people aged 20-70 years.…”
Section: Discussionmentioning
confidence: 99%